Appropriateness of anticoagulation level in older adult patients on Warfarin: A multicenter retrospective study - Amal M. Badawoud; Abdalrhman Alanizi; Adel O. Alnakhli; Wafa Alzahrani; Hadil S. AlThiban; Reema W. AlKhurayji; Anwar Mansour Alnakhli; Jawaher Abdullah Alamoudi; Majed S. Al Yami (Elsevier, 2024)
Warfarin is favored over newer direct oral anticoagulants (DOACs) for many older adults. However, its use necessitates rigorous monitoring due to the fine line between toxic and therapeutic doses. Few studies have evaluated the anticoagulation quality of warfarin among elderly patients in Saudi Arabia. This study aimed to assess and identify factors affecting the anticoagulation quality of warfarin using the time in the therapeutic range (TTR) among older adults attending two hospitals in Saudi Arabia. Additionally, we aimed to evaluate differences in the anticoagulation quality of warfarin when managed by pharmacists or physicians. This cross-sectional study was conducted at King Abdullah bin Abdulaziz University Hospital (KAAUH) and King Fahad Medical City (KFMC) in Riyadh, Saudi Arabia. After calculating the TTR of each patient, the anticoagulation control level was determined using these values: a) good control: >70 %; b) intermediate control: 50-70 %; c) poor control: <50 %. A total of 132 patients prescribed warfarin therapy for different indications were included. Most patients (45.5 %) had poor control with TTRs < 50 %, while 18.2 % had intermediate control, and 36.4 % had good control.Our exploratory findings suggest that having three or more comorbidities was a significant factor associated with a poor TTR [odds ratio (OR) = 3.36; (95 % confidence interval 1.28-8.81); P = 0.014]. Thus, the anticoagulation quality of warfarin among older adult patients was poor in two Saudi Arabian tertiary hospitals, and the number of comorbidities was a potentially poor TTR predictor.